Literature Review: The Description of the Stunting Memory Program Evaluation as an Effort to Optimize the Decline in the Stunting Incidence in the Pandemic Covid-19 Era: Literatur Review: Gambaran Evaluasi Program Penanggulangan Stunting sebagai Upaya Optimalisasi Penurunan Angka Kejadian Stunting di Era Pandemi Covid-19 - Faraiesa Nurahadiyatika; M Fikri Himmawan (Amerta Nutrition, 2022)
Background: Stunting is included in the category of chronic nutritional problems in children which is currently a top priority for nutritional problems in Indonesia. The condition of stunting can be described through the nutritional status of under-five during the growth and early development period of life caused by a lack of child nutrition at the age of the golden period or the 1000 HPK period (the first 1000 days of life). The prevalence of stunting in Indonesia reached 24.4% in 2021, which has decreased from 2018, which was 30.8%, this figure is high when compared to the world's stunting prevalence of (21.7%). The stunting prevention and control program (children born shortly) during the Covid-19 pandemic still needs to be reviewed and re-evaluated to optimize efforts to reduce the incidence of stunting. Objective: Knowing the description of the evaluation of the stunting prevention program as an effort to optimize the reduction in the incidence of stunting in the Covid-19 Pandemic era. Discussion: This journal article was written with inclusion criteria related to the stunting prevention program from 2021 to 2022 during the Covid-19 pandemic. The focus of the stunting prevention program led to the selection of ten journal articles for review in the writing of this journal article. According to the findings of the literature review, the evaluation of stunting prevention programs during the Covid-19 pandemic was quite good when implemented offline. Directly implemented programs effectively increase understanding of the intended research objectives. The results obtained through the stunting prevention program are aimed at research objectives, namely, the aim is to understand and understand the dangers of stunting in children, how to treat and prevent stunting in children, and how to prepare solid complementary food or healthy complementary food for stunted children. Conclusion: The health coaching approach to stunting targets uses various educational media and the provision of MP-ASI and PMT, which has been extensively researched, and is considered very effective in increasing public awareness paying attention to health, especially fulfilling nutrition during the Covid-19 pandemic, so that efforts to reduce the incidence rate of stunting can be optimized.